Leadership First: The Art of Leading - Love, Derrick (Advances in Social Sciences Research Journal, 2022)
Effective leadership begins with an understanding of self and the ability to look beyond oneself to see, project, and inspire others to grow. In this article, readers will reflect on their leadership practices and core fundamental beliefs of what it means to lead and how to effectively produce great results in the people they lead. Leadership is a continuous growth process, and leaders must be willing to engage and self-reflect daily to maximize the capacity of those around them.